Swallow me whole - Powell, Nate 1978- (Top Shelf Productions, 2008)
Swallow Me Whole is a love story carried by rolling fog, terminal illness, hallucination, apophenia, insect armies, secrets held, unshakeable faith, and the search for a master pattern to make sense of one's unraveling. In his most ambitious book to date, Nate Powell quietly explores the dark corners of adolescence -- not the clichéd melodramatic outbursts of rebellion, but the countless tiny moments of madness, the vague relief of medication, and mixed blessing of family ties. As the story unfolds, two stepsiblings hold together amidst schizophrenia, obsessive compulsive disorder, family breakdown, animal telepathy, misguided love, and the tiniest hope that everything will someday make sense
Keywords: Powell, Nate -- 1978-; Graphic novels; Underground comics; Adolescence -- Comic books, strips, etc; Schizophrenia -- Comic books, strips, etc; Stepfamilies -- Comic books, strips, etc; Psychische Störung; Comic